2022
DOI: 10.3390/en15030960
|View full text |Cite
|
Sign up to set email alerts
|

A Redesign Methodology to Improve the Performance of a Thermal Energy Storage with Phase Change Materials: A Numerical Approach

Abstract: In recent years, phase change materials (PCMs) have been presented as a suitable alternative for thermal energy storage (TES) systems for solar water heater (SWH) applications. However, PCMs’ low thermal conductivity and the high dependence on external conditions are the main challenges during the design of TES systems with PCMs. Design actions to improve the performance of the TES systems are crucial to achieve the necessary stored/released thermal energy and guarantee the all-day operation of SWHs under spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Table 3 shows that the maximum outlet water temperature in the present study was always higher than that obtained by ref. [27,36,37]. This can be explained by the using of the higher melting temperature PCM (50 • C) compared to the previous studies.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Table 3 shows that the maximum outlet water temperature in the present study was always higher than that obtained by ref. [27,36,37]. This can be explained by the using of the higher melting temperature PCM (50 • C) compared to the previous studies.…”
Section: Resultsmentioning
confidence: 70%
“…The majority of this research asserted that it showed the beneficial effects of adding PCMs in terms of various methods and criteria, including system efficiency, energy storage capacity, shifting hours, and energy savings. In order to present the practicality of the proposed system and its efficiency in comparison with other proposed systems, the maximum outlet water temperature and the highest thermal efficiency obtained from the proposed system were compared to that obtained by the previous studies [27,36,37] and presented in Table 3. The literature shows a limited number of investigations on PCM thermal storage tanks coupled with a solar thermal collector to provide domestic hot water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal storage systems based on phase change materials (PCM) allow for high energy storage density with very small temperature variations. A thermal energy storage system with PCM [1] in the configuration of a heat exchanger has been redesigned, concluding that the type, encapsulation shape, and amount of PCM slightly impacted the system's performance; however, selecting a suitable sensible heat storage material had the highest impact on meeting the system's targets. A PCM storage system, which therefore utilizes the latent heat of fusion energy, can store from 5 to up to 14 times more heat per unit of volume than a system based only on sensible energy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising strides in solar energy applications, challenges persist, including intermittency, lower thermal efficiency compared to conventional sources, and temporal imbalances [4]. Addressing these hurdles requires tapping into the energy storage capabilities of specific materials to guarantee availability when required [5].…”
Section: Introductionmentioning
confidence: 99%